BUGIS DI KERAJAAN MELAYU: EKSISTENSI ORANG BUGIS DALAM PEMERINTAHAN KERAJAAN JOHOR-RIAU-LINGGA-PAHANG - SYAHRUL RAHMAT (PERADA, 2019)
The geographical conditions of the Malay Peninsula as the trade traffic in the Southeast Asian region make this area a destination for shipping from various ethnic groups in the archipelago as well as from other parts of the world, including the Bugis people from the southern Sulawesi mainland. In its development, in addition to make a living, they gradually begin to join the government structure of the Johor-Riau-Lingga-Pahang Kingdom. Bugis existence in the government structure experiences its own dynamics towards the kingdom which later changes its name to the Kingdom of Riau Lingga. This research is a historical study with a focus on the political dynamics and the existence of Bugis in the Malay Kingdom in the 17th to 18th century. Besides changing the structure of government, the position as Yang Dipertuan Muda, which was held by descendants also gives changes to the development of the kingdom. Even so, Yang Dipertuan Muda must face internal conflicts in the kingdom due to their dominance in the government administration.